Vaccination of Adult Patients with Systemic Lupus Erythematosus in Portugal - Moraes-Fontes, MF (2016)
In the wake of the Portuguese vaccination program 50th anniversary it seems appropriate to review vaccination in patients with systemic lupus erythematosus. Controversial issues as regards the association between autoimmune diseases, infections, and vaccines are discussed as well as vaccine safety and efficacy issues as regards chronic immunosuppressant (IS) drug therapy. After a brief overview of national policies, specific recommendations are made as regards vaccination for adult patients with SLE with a particular focus on current IS therapy and unmet needs.